Value Dynamics in Cross-Sector Development Partnerships: The Case of Taylors of Harrogate and the Food Retail Industry Challenge Fund - Farley, Isla (2015)
Partnerships between organisations from different sectors are increasingly regarded as an effective approach for tackling global development challenges such as extreme poverty, social inequality, environmental degradation and climate change. Cross-sector development partnerships (CSDPs) aim to create value, that is to produce benefits, both for wider society and for the individual organisations involved. However, such partnerships are complex, bringing together organisations with different values, motivations and world-views. This complexity raises a number of significant challenges which need to be understood if CSDPs are to contribute to achieving equitable and sustainable development. This research contributes to understanding two key elements of the value dynamics within CSDPs. The first concerns how organisations define ‘value’ within a partnership, and the second relates to how a satisfactory balance of value (BoV) is achieved and maintained throughout the life of a partnership. The research is based on a case study, exploring a CSDP conducted under the Department for International Development’s (DFID) Food Retail Industry Challenge Fund (FRICH). The project brought together Taylors of Harrogate (ToH), the Ethical Tea Partnership (ETP) and the Rainforest Alliance (RA) in an effort to improve access to European markets for Burundian tea farmers. Three semi-structured interviews were conducted, one with a representative of each organisation. These provided the main source of data, and were supplemented by supporting data from follow-up questions and documentary data. Thematic analysis was carried out on the data, facilitated by the use of NVivo software. The research findings suggest that value definition is an iterative process which takes place throughout the life of a partnership rather than solely before it begins as some literature suggests. Unforeseen circumstances were identified as a significant threat to the BoV within CSDPs. Threats to BoV were partly managed through the redefinition of the value construct, but also through a process of rationalisation through which the partner organisations identified both the remaining value creation potential of the existing project and the potential future value creation opportunities it had opened up. The research highlights the significance of clear value definition at the outset of a CSDP, but also the importance of flexibility from partner organisations as the meaning of value is redefined throughout the life of a partnership. It reemphasises the value that previous collaboration experience can bring to a CSDP, but more specifically with regard to managing partner expectations, and as a facilitator of the rationalisation process which helps to maintain a satisfactory BoV for all partner organisations. The research contributes to the partnership and value creation literature by pushing towards a more nuanced understanding of the dynamics of value within CSDPs.